The new global law - Domingo, Rafael, 1963- (Cambridge [U.K.] ; New York, N.Y. : Cambridge University Press, 2010)
"The dislocations of the worldwide economic crisis, the necessity of a system of global justice to address crimes against humanity, and the notorious "democratic deficit" of international institutions highlight the need for an innovative and truly global legal system - one that permits humanity to reorder itself according to acknowledged global needs and evolving consciousness." "A new global law will constitute, by itself, a genuine legal order and will not be limited to a handful of moral principles that attempt to guide the conduct of the world's peoples. If the law of nations served the hegemonic interests of ancient Rome and international law served those of the European nation-state, then a new global law will contribute to the common good of all humanity and, ideally, to the development of durable world peace. This volume offers a historical-juridical foundation for the development of this new global law."--BOOK JACKET.
The IUS gentium, a Roman concept -- The IUS commune, a medieval concept -- International law, a modern concept -- The crisis of international law -- Global law, a challenge for our time -- The global legal order -- Legal principles of global law -- Conclusion : The third time is the charm.
Includes bibliographical references and index.
Keywords: International law; Law and globalization; Droit international; Droit et mondialisation